Peritoneal Equilibration Test in Costa Rica: Discrepancies from Other Populations - Marta Avellan-Boza; Fabio Hernández; Allan Ramos-Esquivel (International Journal of Nephrology)
Objective. Continuous Ambulatory Peritoneal Dialysis (CAPD) is a kidney replacement therapy that has been recently incorporated in developing countries. We aim to establish our reference values, to compare them with the original and the Mexican population, and to associate some variables with the type of peritoneal transport. Methods. Thirty peritoneal equilibration tests (PET) were performed. The ratio for D/P creatinine and the D/D0 ratio for glucose were calculated and compared to reference values. We conducted a retrospective analysis to correlate peritoneal transporters with some predictive variables. Results. D/P creatinine ratio at 2 hours, D/D0 glucose ratio at 4 hours, and net ultrafiltrate volume (nUFV) were significantly different from those reported by Twardowski et al. The results documented in the Mexican population only coincide with our results for the D/P creatinine ratio at 4 hours. Any of the studied variables were associated with a specific type of peritoneal transport. Conclusions. Peritoneal permeability among Costa Rican CAPD patients is different from the original population described by Twardowski et al. and from other Latin-American population. This supports the theory that ethnical differences could be responsible for such variations and they validate our statement that each region should possess value references of their own.